Education, Unemployment, Poverty on Economic Growth in East Java Province - Ifa Azzahra Farhatannisa; Muhammad Wakhid Musthofa (JURNAL ILMIAH EDUNOMIKA, 2025)
Economic development in a country or region can be seen from several indicators of an economy, including unemployment, poverty and education. This study aims to analyze the influence of education, unemployment and poverty on economic growth in East Java Province for the period 2010-2023. The data sources used in this study are secondary data in the form of time series data . The method used is multiple linear regression analysis and Ordinary Least Square (OLS) estimation. The results of the study The t-test of education has a significant effect on economic growth in East Java, unemployment has a significant effect on economic growth in East Java and poverty has a significant effect on economic growth in East Java. The results of the F-test show that the variables Education, unemployment and poverty have a significant effect simultaneously on economic growth in East Java. Local governments, communities or the private sector can take strategic steps to improve the quality of education, reduce unemployment and can alleviate poverty problems in East Java.